Four Myths About Unauthorized Subcontracting - Caro, Felipe; Lane, Leonard; de Tejada Cuenca, Anna (MIT Sloan Management Review, 2021)
Unauthorized subcontracting is a problem for companies that are trying to improve supply chain transparency. The authors' new research identifies what drives suppliers to divert orders - and upends the conventional wisdom about which suppliers are most at risk of engaging in this behavior. Organizations seeking better visibility into supplier practices can use analytics to predict the likelihood of diverted orders. But they also need to consider how their own buying practices may be a factor.
Online resource; Title from title page (viewed September 8, 2021)
Keywords: Subcontracting